Root canal treatment of mandibular second premolar with four root canals - Bander Al-Abdulwahhab; Saad Al-Nazhan (Saudi Endodontic Journal, 2015)
Variation in the morphology of the root canal system of mandibular premolars has been demonstrated. This diverse morphology challenges for the clinician to clean, shape, and fill the entire root canal system. A case report of a mandibular second premolar with four root canals separated at the apical third and underwent endodontic treatment is presented.